ASPEK HUKUM BENDA TIDAK BERGERAK SEBAGAI OBYEK JAMINAN FIDUSIA - celine tri siwi (Warmadewa Press, 2017)
Abstract This study aims to find and analyze legal aspects immovable as a fiduciary guarantee object. This study is a normative law by using four (4) approach: statutory approach, conceptual approach, an analytical approach and case approach. Collection and processing of legal materials both primary and secondary legal materials relating to the fiduciary. Furthermore, identified with the rule of law that is directly related to the formulation of research problems, from identification, systematization conducted research material has been collected. Descriptive analysis was then performed with a coherent explanation. The results of this study explained that with regard to the legal aspects of the object is not moving as fiduciary object can be categorized into 3 (three) period, namely a period before Law 4 of 1996 on Mortgage, the period after the enactment of Law No. 4 of 1996 on Mortgage, and the period after the Law No. 42 of 1999 on Fiduciary. The provisions concerning immovable object here is to accommodate the credit needs for building owners without rights on land where the building has a high economic value in accordance with the principle of horizontal separation. Keywords: legal aspects, immovable, fiduciary